Clinical Importance of Imaging Anatomical Signs in Predicting Transverse Sinus Dominance Using Conventional Magnetic Resonance Imaging - AL-Ani, Maryam I.; Fahed , Qusay A.; Shyaa , Ali I. (Journal of the Faculty of Medicine Baghdad, 2023)
Background: Differentiating flow gaps associated with hypoplastic transverse sinus from venous thrombosis is a diagnostic challenge in brain magnetic resonance imaging with venography. Objectives: To assess the clinical benefit of anatomical signs to anticipate the side of the dominant transverse sinus. Methods: A total of 100 patients underwent brain magnetic resonance imaging with venography at the radiology department /medical city and were retrospectively reviewed for the direction of superior sagittal sinus flow void, inclination of sulcus for the superior sagittal sinus, angulation of the posterior falx and direction of occipital lobe bending in axial non-contrast T1 weighted image, then compare these findings with a side of the dominant transverse sinus in magnetic resonance venography. Results: Inclination of sulcus for superior sagittal sinus and superior sagittal sinus flow void direction toward the right side had high positive predictive values (95.5%) and (93.2 %) in proper matching with the right transverse sinus dominance, respectively. Right-sided angulation of the posterior flax and rightward direction of the occipital lobe had a positive predictive value of (90.9 %) in predicting transverse sinus dominance. Conclusion: The side of dominant transverse sinus can be anticipated by reviewing anatomical signs in T1 weighted image, which may help to differentiate hypoplastic transverse sinus from venous thrombosis that aid in better interpretation of brain MRI- MRV examinations.